Аcanthamoeba keratitis and outcomes of the treatment (clinical cases) - M. M. Bikbov; V. K. Surkova; E. L. Usubov; N. A. Nikitin (Oftalʹmologiâ, 2016)
Acanthamoeba keratitis (AK) — corneal inflammation caused by protozoa — Acanthamoeba. The disease is related mainly with wearing of contact lens, pathogen — Acanthamoeba penetrates under the contact lenses. The cases of AK after Lasik are described. Corneal epithelium microtrauma and contact with sources of environmental pollution are the risk factors of the invasion of Acanthamoeba into the cornea.Acanthamoebas affect soil, stagnant reservoirs, swimming pools, drain pipes, tap water, etc. Diagnosis can be confirmed only when cysts are detected in cornea material, plate count, smear, and the containers where such material is stored. Long life cycle including cyst stage helps keratitis relapsing course last for months. It is not always possible to detect cysts. Assessment of etiology presents certain difficulties.Such aspects as history taking, monitoring the clinical course of disease, confocal microscopy that enables to reveal acanthamoebas in vivo help to determine a diagnosis.Disease is characterized by a long chronic course with the development descemetocele and cornea perforation. The sequence of remissions and exacerbations of inflammation, apparently, occurs due to peculiarities of Acanthamoeba life cycle. Acanthamoeba keratitis is difficult to treat, it’s resistant to antibiotics. Untimely diagnosed disease and delayed initiation of treatment in patients with AK promote corneal perforation and inflammatory process in deep eye structures what often leads to eye enucleation.Severe pain is typical for AK in onset of disease. It is caused by emergence of subepithelial infiltrates and defects along the nerve fibers located in the most sensitive surface layer of the cornea. Conservative treatment is conducted with the use of antiseptics. The most effective one against cysts is 0.02% chlorhexidine which is prepared ex. temporae.The article presents the peculiarities of clinical course of Acanthamoeba keratitis, clinical cases of the disease and the results of penetrating keratoplasty as the main method of treatment of severe AK.